AN ANALYSIS OF ENGLISH STUDY PROGRAM STUDENTS FKIP UNIVERSITAS RIAU RECEPTIVE SKILLS THROUGH TOEFL SCORE - Dwi Septiyana; Erni Erni; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aimed to analyse the English receptive skills through the TOEFL score map of the English Study Program Students FKIP Universitas Riau. This research was descriptive quantitative research, with 95 students as the sample. This research used students TOEFL scores that the researcher got from UPT Bahasa Universitas Riau. Analysing students’ TOEFL scores showed that only 55,7% of students had passed the test and students classified as advanced level only 50,5%. Students’ receptive skills, either who passed or failed the TOEFL test, still faced difficulties answering the listening comprehension section questions, especially about short conversations and mini-talks. There is an imbalance in the students’ receptive skills because the students can understand had better in the reading comprehension section than in the listening comprehension section.Key Words: Analysis, Receptive Skills, TOEFL score